Uji Kinerja Portable Rainfall Simulator pada Berbagai Tekanan Pompa - Ridwan Ridwan; Oktafri Oktafri; Muhammad Amin; Maya Ardila (Jurnal Agricultural Biosystem Engineering, 2022)
Rainfall simulator is a tool that allows you to create artificial rain simulation as you wish.  Rainfall simulator can be used to study runoff, erosion, infiltration, and other events in hydrological processes on a laboratory scale.  The purpose of the study was determine the performance of the portable rainfall simulator that had been made with test parameters, namely the discharge radiance value, nozzle constanta, and uniformity coefficient.  The test carried out using three variatons of pump pressure treatment, namelay 1.0, 1.3, and 1.6 bar and each treatment was repeated 3 times with a test time of 7.5 minutes.  The test result show that the portable rainfall simulator can produce water discharge with uniformity level (CU) greather than 70%.  The best pump pressure for the highest uniformity of transmission is 1.6 bar. The pumping pressure affects the water discharge with a uniformity coefficient value (CU), the greather the pump pressure, the greather the water discharge value, and the uniformity coefficient value (CU). The type of nozzle used is good enough to be used as a transmitter from the rainfall simulator that was made. Keywords: Coefficient Uniformity (CU), Discharge, Nozzle, Rain, Rainfall Simulator, Water.